2015
DOI: 10.1177/0284185114568908
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging for evaluating lymph node eradication after neoadjuvant chemoradiation therapy in locally advanced rectal cancer

Abstract: Adding DWI to T2W imaging provided no additional diagnostic benefit for the evaluation of LN eradication following CRT in patients with LARC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…yN0 stage) after CRT on a patient basis. 47,48 Van Heeswijk et al reported that the visual absence of nodes on DWI after CRT was a highly reliable predictor of a negative nodal status (sensitivity 100%), but the presence of nodes on post-CRT DWI was an unspecific finding, which could indicate either the presence of benign or malignant nodes, resulting in a low specificity of only 14%, again illustrating the limited capacity of DWI to visually characterize lymph nodes. 47 Ryu et al used a confidence level score to predict lymph node eradication after CRT with and without DWI and found no improvement in diagnostic performance for DWI compared to T 2 W-MRI with AUCs in the same range of 0.77-0.80.…”
Section: Nodal Restagingmentioning
confidence: 99%
“…yN0 stage) after CRT on a patient basis. 47,48 Van Heeswijk et al reported that the visual absence of nodes on DWI after CRT was a highly reliable predictor of a negative nodal status (sensitivity 100%), but the presence of nodes on post-CRT DWI was an unspecific finding, which could indicate either the presence of benign or malignant nodes, resulting in a low specificity of only 14%, again illustrating the limited capacity of DWI to visually characterize lymph nodes. 47 Ryu et al used a confidence level score to predict lymph node eradication after CRT with and without DWI and found no improvement in diagnostic performance for DWI compared to T 2 W-MRI with AUCs in the same range of 0.77-0.80.…”
Section: Nodal Restagingmentioning
confidence: 99%
“…Lymph node size, morphology, or both, typically based on MRI, appear to correlate with residual metastases . The reported accuracy of MRI in assessing complete response in initially involved lymph nodes ranges from 80% to 90%, with additional techniques such as contrast enhancement potentially improving these rates . Because of the potential predictive value of MRI, it has been incorporated by some groups into the assessment of cCR.…”
Section: Introductionmentioning
confidence: 99%
“…22 Our study included DWI but there was not increased concordance between pathologie and post treatment MRI staging lymph nodes (LN) evaluation is not clear. Ryu et al 23 evaluated the added value of DWI in the evaluation of LN eradication after CRT in patients with LARC. Pathological reports served as the reference standards for LN eradication.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that adding DWI to T2W imaging provided no additional diagnostic benefit for the evaluation of LN eradication following CRT in patients with LARC. 23 Results of a meta-analysis showed that none of the three commonly used imaging modalities used in rectal cancer can provide reliable evaluation on regional LN metastasis. Perhaps we should conduct further research on specific contrast agents or functional imaging to try and improve the accuracy.…”
Section: Discussionmentioning
confidence: 99%